Protective Mechanism of Fagopyrum esculentum Moench. Bee Pollen EtOH Extract Against Type II Diabetes in a High-Fat Diet/Streptozocin-Induced C57BL/6J Mice - Zhang, Jinjin; Cao, Wei; Zhao, Haoan; Guo, Sen; Wang, Qian; Cheng, Ni; Bai, Naisheng (Frontiers in Nutrition, 2022)
Bee pollen is known as a natural nutrient storehouse and plays a key role in many biological processes. Based on the preliminary separation, identification, and characterization of the main active components of Fagopyrum esculentum Moench. bee pollen (FBP), the protective effects of F. esculentum bee pollen extract (FBPE) on high-fat-diet (HFD) and streptozocin (STZ) induced type II diabetes mellitus (T2DM) was evaluated in this study. The results revealed that FBPE contains 10 active compounds mainly including luteolin (9.46 g/kg), resveratrol (5.25 g/kg), kaemferol (3.67 g/kg), etc. The animal experiment results showed that FBPE could improve HFD-STZ induced T2DM mice. Moreover, the underlying mechanism of the above results could be: (i) FBPE could reduce the inflammation related to phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway, and (ii) the gut microbiota remodeling. The results of correlation analysis showed Candidatus Arthromitus and SMB53 indicated positive correlations to tumor necrosis factor-α (TNF-α); Coprococcus, Ruminocossus, and Odoribacteraceae reported negative correlations to transforming growth factor-β (TGF-β). That FBPE has an outstanding ability to improve T2DM and could be used as a kind of potential functional food for the prevention of T2DM.